Best practices in global governance. Issue 3 (9th January 2017) - Bernstein, Steven; van der Ven, Hamish
Abstract: Best practices are increasingly used to govern a range of global issues. Yet, the rise of global governance through best practices has received scant attention in the International Relations literature. How do best practices differ from other modes of governance? How are they constructed? And to what end? We offer a novel conceptualisation of best practices as a unique mode of global governance principally distinguished by basing claims of political authority on existing practices. Belying their apolitical terminology, best practices in global governance are purposively constructed by political actors to steer targeted actors toward desired ends. We illustrate the characteristics of governance through best practices with reference to state and non-state global governance initiatives in a wide range of issue areas, ranging from finance and development to human rights and the environment, and through an in-depth case study of the ISEAL Alliance, a disseminator of best practices for transnational sustainability standard-setters. We find that governance through best practices has both positive and negative consequences. While it offers a pragmatic approach to global governance under conditions of fragmentation and polycentricity, it can also mask underlying power dynamics and political agendas and therefore requires ongoing critical scrutiny.